Intuitionistic fuzzy parameterised fuzzy soft set - El-Yagubi, Entisar; Abdul Razak Salleh (Penerbit Universiti Kebangsaan Malaysia, 2013)
In this paper, the definition of intuitionistic fuzzy parameterised fuzzy soft set (ifpfs-sets) is introduced with their properties. Two operations on ifpfs-set, namely union and intersection are introduced. Also, some examples for these operations are given. The definition of ifpfsaggregation operator which forms ifpfs-decision making method is introduced